2015
DOI: 10.1177/0022034514566215
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Gene Polymorphism and Environmental Factor in the Risk of Oral Cancer

Abstract: Oral squamous cell carcinoma is a common neoplasm that is known to be causally associated with genetic factors and environmental carcinogens. The receptor for advanced glycosylation endproducts (RAGE) is a transmembrane protein of the immunoglobulin superfamily with broad specificity for multiple ligands, and it has been shown to play vital roles in several pathophysiologic processes, including diabetes, Alzheimer disease, renal disease, cardiovascular disease, and cancer. The present study aimed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 40 publications
3
45
1
Order By: Relevance
“…Furthermore, a genome-wide association study performed on 8,605 upper aerodigestive cancer cases and 11,405 controls from the INHANCE consortium, identified five polymorphisms implicated in cancer susceptibility: three variants in the ADH gene cluster (rs1573496-ADH7, rs1229984-ADH1B, and rs698-ADH1C) and two variants (rs149496-4q21 and rs4767364-12q24) located near DNA repair genes and ALDH2 gene, respectively [27]. More recently, Su et al [28] have identified four SNPs in the receptor for advanced glycosylation end products (RAGE) gene which in association with betel quid chewing and/or tobacco use conferred increased risk for oral cancer in subjects with particular haplotypes of the 4 RAGE SNPs. These polymorphisms could represent inherited genetic factors which in combination with environmental mutagens may predispose subjects to head and neck cancer.…”
Section: Tobacco Smoke Alcohol Consumption and Head And Neck Cancersmentioning
confidence: 99%
“…Furthermore, a genome-wide association study performed on 8,605 upper aerodigestive cancer cases and 11,405 controls from the INHANCE consortium, identified five polymorphisms implicated in cancer susceptibility: three variants in the ADH gene cluster (rs1573496-ADH7, rs1229984-ADH1B, and rs698-ADH1C) and two variants (rs149496-4q21 and rs4767364-12q24) located near DNA repair genes and ALDH2 gene, respectively [27]. More recently, Su et al [28] have identified four SNPs in the receptor for advanced glycosylation end products (RAGE) gene which in association with betel quid chewing and/or tobacco use conferred increased risk for oral cancer in subjects with particular haplotypes of the 4 RAGE SNPs. These polymorphisms could represent inherited genetic factors which in combination with environmental mutagens may predispose subjects to head and neck cancer.…”
Section: Tobacco Smoke Alcohol Consumption and Head And Neck Cancersmentioning
confidence: 99%
“…More than 30 gene polymorphisms in RAGE have been identified in multiple cancers, including renal caner, oral cancer, breast cancer, colorectal cancer, lung cancer, ovarian cancer, pancreatic cancer, nasopharyngeal carcinoma, and gastric cancer (Cheng et al, 2005; Chocholaty et al, 2014; Gu et al, 2008; Krechler et al, 2010; Pan et al, 2013; Qian, Sun, Zhang, Ke, & Zhu, 2014; Su, Chien, Lin, Chen, & Yang, 2015; Zhang et al, 2013; Zhou, Deng, Li, Yin, & Ye, 2014). A comprehensive meta-analysis suggested that the 82G/S polymorphism (3374 cancer cases vs. 3757 controls) in the RAGE promoter region is associated with a significantly increased risk of cancer, where −374T/A polymorphism (2936 cancer cases vs. 3,338 control) is associated with a reduced risk of cancer (Xia et al, 2015).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%
“…Oral cancer is a subclass of head and neck cancer with substantial morbidity and mortality, and the worldwide incidence is estimated to be ∼275,000 cases annually . Epidemiological studies have indicated that smoking, betel nut chewing, and alcohol consumption are predominant risk factors triggering oral cancer . Oral cancer possesses high local invasiveness and great metastatic ability in cervical lymph nodes with poor patient prognoses.…”
Section: Introductionmentioning
confidence: 99%